If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) = 7 + -2x Reorder the terms: 2(-5 + x) = 7 + -2x (-5 * 2 + x * 2) = 7 + -2x (-10 + 2x) = 7 + -2x Solving -10 + 2x = 7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -10 + 2x + 2x = 7 + -2x + 2x Combine like terms: 2x + 2x = 4x -10 + 4x = 7 + -2x + 2x Combine like terms: -2x + 2x = 0 -10 + 4x = 7 + 0 -10 + 4x = 7 Add '10' to each side of the equation. -10 + 10 + 4x = 7 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = 7 + 10 4x = 7 + 10 Combine like terms: 7 + 10 = 17 4x = 17 Divide each side by '4'. x = 4.25 Simplifying x = 4.25
| 3sinx-4cosx-2=0 | | .2(7-x)=4 | | 5-3x-(-4x+6)=-(8x+11)-(3x-10) | | 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 | | (7+y)(5y+3)= | | 11x+35+35=180 | | 3p-42=31 | | 1-0.4=2 | | 18x-4+4x=172 | | 8w+12-6w=5(w+3)-2w | | a^2-16a+63=0 |